Hubungan Antara Self Compassion dan Resiliensi Pada Mahasiswa Tingkat Akhir - Syahputra, Anda; Abdurrahman, Abdurrahman (Universitas Malahayati, 2024)
ABSTRACT Final year students are required to complete a final assignment as a graduation requirement. In doing this, students face many obstacles and obstacles. Because this does not cover the possibility of causing students to become anxious, stressed, frustrated and lose motivation. To overcome this, resilience is needed as an effort to minimize the obstacles that occur. The dynamics of resilience within individuals are influenced by self-compassion. This research aims to see the relationship between self-compassion and resilience in final year students. This research uses quantitative research with a correlation approach. Data collection was carried out cross-sectionally. The population is final year students at the North Aceh Nursing Study Program, Aceh Ministry of Health Polytechnic. The sampling technique used a total population technique, so the sample size was 59 people. Data collection used the resilience scale and self-compassion scale (SCS). Data analysis uses correlation tests. Data analysis uses correlation tests. The research results obtained a correlation coefficient value of 0.399 with a Sig value. 0.002, which means it has a strong correlation in the positive direction. So it can be concluded that there is a significant relationship between self-compassion and the resilience variable of final year I students of the North Aceh Nursing Study Program, Health Polytechnic, Ministry of Health, Aceh. The conclusion of this research is that self-compassion is related to the resilience of final year I students of the North Aceh Nursing Study Program, Health Polytechnic, Ministry of Health, Aceh Keywords: Students, Resilience, Self-compassion ABSTRAK Mahasiswa tingkat akhir dituntut untuk menyelesaikan menyelesaikan tugas akhir sebagai syarat kelulusan. Dalam mengerjakannya banyak hambatan dan kendala yang dihadapi oleh mahasiswa. Karna hal ini tidak menutupi kemungkinan membuat mahasiswa menjadi cemas, stress, frutasi dan hilangnya motivasi. Untuk mengatasi hal tersebut perlunya resiliensi sebagai upaya meminimalisir hambatan yang terjadi. Dinamika resiliensi dalam diri individu dipengaruhi oleh self compassion. Penelitian ini bertujuan untuk melihat hubungan self compassion dengan resiliensi pada mahasiswa tingkat akhir. Penelitian ini menggunakan penelitian kuantitatif dengan pendekatan korelasi. Pengambilan data dilakukan secara cross-sectiona. Populasi adalah mahasiswa tingkat akhir di Prodi Keperawatan Aceh Utara Poltekkes Kemenkes Aceh. Tehnik pengambilan sampel menggunkan tehnik total populasi, maka juamlah sampel sebanyak 59 orang. Pengumpulan data menggunakan skala resiliensi dan skala self compassion (SCS). Analisa data menggunakan uji korelasi. Hasil penelitian didapat nilai koefisien korelasi sebesar 0,399 dengan nilai Sig. 0,002, dimana hal ini berarti memiliki korelasi yang kuat kearah positif. Maka dapat disimpulkan bahwa adanya hubungan yang signifikan antara self compassion dengan variabel resiliensi mahasiswa tingkat akhir I Prodi Keperawatan Aceh Utara Poltekkes Kemenkes Aceh. Kesimpulan dari penelitian ini self compassion berhubungan dengan resiliensi mahasiswa tingkat akhir I Prodi Keperawatan Aceh Utara Poltekkes Kemenkes Aceh. Kata Kunci: Mahasiswa, Resiliensi, Self-compassion